Professionellt omdöme som handlingsutrymmets kunskapsform - En kvalitativ studie om socialsekreterares användning av kunskap vid förhandsbedömningar i social barnavård - Engblom,Ida (2026)
Professional judgement is a complex phenomenon to comprehend and is often forgotten when discussing the importance of knowledge use in discretionary decision-making within Swedish child welfare. Therefore, the study had a dual purpose that aimed to foster a deeper understanding of professional judgement in Swedish child welfare; theoretically, the study aimed to explore the meanings of professional judgement and conceptualise its significance in discretionary decision-making. And empirically, the study aimed to operationalise professional judgement as a form of knowledge by investigating knowledge use in the initial assessment of reports regarding concerns of the child. By discussing and analysing theories regarding the importance of phronetic knowledge and discretion in human service organisations, the theoretical purpose was achieved. The empirical purpose was addressed by a qualitative method using semi-structured interviews with eight child welfare social workers from seven different municipalities in the region of Skåne. The theoretical analysis concluded professional judgement as an epistemic dimension of professional discretion. The empirical findings confirmed this conclusion and illustrated how social workers within child welfare use professional judgement as a form of knowledge when performing initial assessments. By presenting a conceptualisation and operationalisation of professional judgement, the study has contributed to a deeper understanding of professional judgement as a significant form of knowledge in Swedish child welfare.
Keywords: professional judgement; phronesis; initial assessment in child welfare; discretionary decision-making; professionellt omdöme; fronesis; förhandsbedömningar i social barnavård; diskretionärt beslutfattande